2009
DOI: 10.1371/journal.pgen.1000760
|View full text |Cite
|
Sign up to set email alerts
|

SOS Response Induces Persistence to Fluoroquinolones in Escherichia coli

Abstract: Bacteria can survive antibiotic treatment without acquiring heritable antibiotic resistance. We investigated persistence to the fluoroquinolone ciprofloxacin in Escherichia coli. Our data show that a majority of persisters to ciprofloxacin were formed upon exposure to the antibiotic, in a manner dependent on the SOS gene network. These findings reveal an active and inducible mechanism of persister formation mediated by the SOS response, challenging the prevailing view that persisters are pre-existing and forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
386
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(429 citation statements)
references
References 73 publications
24
386
3
4
Order By: Relevance
“…Moreover, cell populations enriched for persisters had increased levels of TA mRNAs (33,34), and deletion of yafQ (encoding a RelE homolog) resulted in reduced persistence of cells in a biofilm but not in planktonic cells (32). Interestingly, the type I TA locus tisAB/istR (36) was required for persister generation after induction of the SOS response (37,38). We show here that type II TA loci encoding mRNases are responsible for persister cell formation during exponential growth and during the stationary phase.…”
mentioning
confidence: 99%
“…Moreover, cell populations enriched for persisters had increased levels of TA mRNAs (33,34), and deletion of yafQ (encoding a RelE homolog) resulted in reduced persistence of cells in a biofilm but not in planktonic cells (32). Interestingly, the type I TA locus tisAB/istR (36) was required for persister generation after induction of the SOS response (37,38). We show here that type II TA loci encoding mRNases are responsible for persister cell formation during exponential growth and during the stationary phase.…”
mentioning
confidence: 99%
“…In 2009, Dörr et al 62 analyzed the effect of the fluoroquinolone ciprofloxacin on the formation of persisters. Fluoroquinolones are antibiotics that target DNA gyrase and DNA topoisomerase, ultimately causing DNA lesions which in turn trigger the SOS response.…”
Section: Tisb/istr1 As a Bona Fide Persister Locusmentioning
confidence: 99%
“…The data suggested that these persister were not pre-existing but, at least mostly, were induced to enter this state. 62 E. coli encodes several SOS-induced TA systems (symE/symR, tisB/istR1, hokE/sokE, yafO/yafN, yafQ/dinJ 8 ), and TA genes had previously been found to be among the gene classes that were upregulated in persister cells. 56 In a follow-up paper by the Lewis group, it was shown that ciprofloxacin increased persister levels via SOS-dependent induction of TisB.…”
Section: Tisb/istr1 As a Bona Fide Persister Locusmentioning
confidence: 99%
“…Прежде всего для многих бактерий альтернативой устойчивости является способ-ность адаптации к фторхинолонам, связанная с замедлением метаболизма, репликации ДНК и деления клеток, а также формированием биопленок [13,21,70,84].…”
Section: роль дополнительных механизмов в развитии устойчивости к фтоunclassified
“…Поскольку действие фторхинолонов на-правлено на ДНК, активация систем репара-ции важна для сохранения жизнеспособности [13,21,84]. Это было показано при исследо-вании влияния мутаций по гену ncr, продукт которого является репрессором системы репа-рации RecCBD, на устойчивость Acinetobacter baumannii к ципрофлоксацину.…”
Section: роль дополнительных механизмов в развитии устойчивости к фтоunclassified